THE EFFECTIVENESS USING INQUIRY BASED NATURAL SCIENCE MODULE WITH AUTHENTIC ASSESSMENT TO IMPROVE THE CRITICAL THINKING AND INQUIRY SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Hairida, H. (Jurnal Pendidikan IPA Indonesia, 2016)
The aim of this research is to investigate the effectiveness of inquiry-based science modul with authentic assessment to develop studentsâ inquiry skills and critical thinking. This research employed a quasi experiment method with pretest-posttest control group design. This research is conducted on 7th grade of one of Junior High School in Pontianak, by using 2 classes as a sample. The data was collected by using inquiry skills observation sheets, critical thinking test, and interview. The result shows that the mean of inquiry skills and critical thinking scores of experiment group is higher than the control group, and the significance score from using t-test is (0.00) < 0.05, which means there is a difference of inquiry skills in the experiment and control group. Score of N-gain shows that the mean of experiment groupâs inqury skills and critical thinking score after the treatment, is higher than control group. It concludes that science learning by using inquiry-based modul with authentic assessment is effective to develop studentsâ inquiry skills and critical thinking.